Regulators and competition spurring or retarding innovation in the telecommunications sector? - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2000)
This paper empirically explores how technology policy affects innovation behaviour in the telecommunications sector. Our empirical analysis aims at shedding light on the following highly topical issues: (I) Whether opening up the domestic market to competition spurs innovative activity?, (ii) Whether the presence of independent regulatory agency influence innovation behaviour of telecommunications operators?, and (iii) What is the direction of Granger-causality between innovation creation and technology diffusion in the communications sector? We develop an econometric model that takes into account the dynamic, non-linear nature of the innovation process and interdependency between equations for a patent count variable, R&D and technology diffusion. We use data from 61 major telecommunications operators between the years 1991 and 1996 to investigate how technology policy has influenced their innovative activities, i.e. their R&D expenditures and the number of patent applications, and the diffusion of communications technologies in their domestic markets. – Innovation ; technology diffusion ; telecommunications ; technology policy – – Tutkimus selvittää aineistoanalyysin avulla teknologiapolitiikan vaikutuksia innovaatiokäyttäytymiseen telekommunikaatiosektorilla. Empiirisen analyysin tavoitteena on valaista seuraavia ajankohtaisia kysymyksiä: (I) Kannustaako kotimaisten markkinoiden avaaminen kilpailulle innovaatiotoimintaa?, (ii) Onko riippumattoman sääntelyviranomaisen läsnäololla vaikutusta teleoperaattoreiden innovaatiokäyttäytymiseen?, (iii) Mikä on Granger-kausaalisuuden suunta innovaatioiden kehittämisen ja teknologioiden leviämisen välillä viestintäsektorilla? Tutkimuksessa kehitetään ekonometrinen malli, joka ottaa huomioon innovaatioprosessin dynaamisen, epälineaarisen luonteen sekä keskinäisen riippuvuuden yritysten patentointia, T&K-menoja ja teknologioiden leviämistä kuvaavien yhtälöiden välillä. Raportoidussa empiirisessä tutkimuksessa analysoidaan teknologiapolitiikan vaikutuksia teleyritysten innovaatiotoimintaan - niiden T&K-menoihin ja patenttihakemusten lukumäärään, sekä viestintäteknologioiden leviämiseen yritysten kotimaan markkinoilla - käyttäen aineistoa 61 suuren teleoperaattorin toiminnasta ajanjaksona 1991-1996. – Innovaatio ; teknologioiden leviäminen ; televiestintä ; teknologiapolitiikka
Keywords: 330; Innovation; Innovationsdiffusion; Telekommunikation; Forschungs- und Technologiepolitik; Aufsichtsbehörde; Finnland